Pedagogy of the knife – a case study of the re-authorisation of the personal myth of masculinity. Field of forest pedagogy and cultural psychology - Michał Paluch; Andrzej Pankalla (Studia z Teorii Wychowania)
The title of the article indicates several dimensions of the analyses undertaken: 1) the archetype of the knife as a carrier of unconscious meanings, especially pedagogically and psychologically relevant meanings; 2) the re-authorization of the personal myth as a method of experiencing self-identification, self-therapy and self-education, freeing men from the sources of current restlessness; 3) the crisis of masculinity as a dilemma on the nature-culture axis, posed to men by the current cultural (dis)course. The positive and pedagogical significance of the ‘knife’, which is laden with pejorative connotations, was also emphasised. Research conclusions were derived using the autoethnographic-existential method, based on: 1) a self-description of the author’s experienced experiences, during the ordering of a handmade knife, necessary for the construction of a forest pedagogical settlement for families with children; 2) an interview conducted with a knife maker (blacksmith), on the content of the orders reported to him. An important part of the analysis falls within the perspective of cultural psychology and mythotherapy, undertaken on the grounds of forest pedagogy, as the main theoretical framework. On this basis, the connection and entanglement of an unfulfilled sense of masculinity with a probable deficit in the experience of independence (fighting for freedom, protecting the family, defending the territory) was discovered. It follows that they are deeply rooted in Polish history and the intergenerational nature of familialism, and can make themselves known in the form of activities that are only seemingly mundane.